“Efecto de la aplicación foliar de Nitrógeno, Calcio y Boro sobre el rendimiento del cultivo de arroz (Oryza sativa L.)”. - Carpio Cerna, Shirley Lisbeth (2018)
VIII. SUMMARY The present experimental work was carried out on the grounds of the Experimental Farm "Palmar", which belongs to the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km. 10.5 of the Babahoyo - Montalvo highway. Its objective was to evaluate the effect of foliar application of Nitrogen, Calcium and Boron on rice crop yield. The SFL-11 rice variety was cultivated in plots of 12 m2, where 7 types of fertilizers were evaluated: Ammonium Nitrate, Sett Calcium Boron, Folcrop Ca-B, Calcium Nitrate, Borax, Promet Ca and Newfol B, the same that were applied alone and in mixtures with different doses, in ten treatments and three repetitions with the experimental design complete randomized blocks. The evaluation and comparison of means were performed with the Tukey test at 95% of probabilities. At the end of the crop cycle, the following were evaluated: plant height, number of tillers per m2, panicle number per m2, panicle length, number of grains per panicle, days to flowering, foliar analysis, days to physiological maturity, weight of thousand grains, yield per hectare and economic analysis. The results determined in the evaluated variables that height of plant, filled grains per panicle, empty grains per panicle, tillers per m2, panicles per m2, weight of a thousand grains, days to flowering, and yield per hectare presented high statistical significance. They did not influence the variables panicle length, ripening days and grain-straw ratio By applying Borax with a dose of 1 kg / ha, the highest yield was obtained (7513.67 kg / ha), and the highest economic benefit ($ 1093.09). Key words: rice, foliar, nitrogen, calcium, boron, yield.